Challange Challenge-Based Learning as a Pedagogical Catalyst for Literacy in Fifth Grade Elementary School Students - Dewi Novi Yanti; Yunus Abidin; Dede Tri Kurniawan (MIMBAR PGSD Undiksha, 2026)
Reading literacy skills among elementary school students, specifically in understanding, interpreting, and evaluating information, remain suboptimal due to conventional teaching practices focused on one-way knowledge transfer. This study critically evaluates the effectiveness of Challenge-Based Learning (CBL) as a pedagogical catalyst for enhancing and synthesizing the literacy skills of fifth-grade elementary students. Employing a quantitative approach with a pre-experimental one-group pretest-posttest design, the study involved 27 students selected via purposive sampling. The research instrument comprised a literacy test covering literal, interpretive, and evaluative domains. Data were analyzed using descriptive statistics and a paired sample t-test. The results demonstrated a significant increase in the average literacy scores after the implementation of the CBL model (p < 0.05). These findings confirm that challenge-based learning stages effectively activate higher-order thinking processes and reflective student engagement. In conclusion, this study confirms that CBL serves as an effective transformative model for advancing critical literacy competencies. The practical implication suggests that educators should integrate real-world challenges into the curriculum to better prepare students for the information complexities of the 21st century.